1986
DOI: 10.1149/1.2108758
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoric Acid Absorption and Performance of Gas Diffusion Electrode

Abstract: The present study was directed towards investigating the relationship between the acid absorption of the catalyst layer and electrode performance and discussing the pores available for the cathode and anode reactions. The catalyst layer was formed on a porous carbon substrate by spreading a slurry consisting of a carbon‐supported platinum catalyst and PTFE dispersion. The nonionic surfactant contained in the dispersion enhances the acid absorption. Pores from 0.2 to 10 μm in diameter are available for the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…On the other hand, Pt loading in electrodes is still high in a system using liquid state electrolyte such as high temperature PEMFC and phosphoric acid fuel cells (PAFC) [20][21][22][23][24][25][26][27][28][29][30]. Because the liquid state PA cannot be fixed around catalyst, the maximum TPB and the optimum amount of electrolyte in electrodes are difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Pt loading in electrodes is still high in a system using liquid state electrolyte such as high temperature PEMFC and phosphoric acid fuel cells (PAFC) [20][21][22][23][24][25][26][27][28][29][30]. Because the liquid state PA cannot be fixed around catalyst, the maximum TPB and the optimum amount of electrolyte in electrodes are difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…The arrangement of the single cell was the same as those reported in the previous paper [15,16]. Acid absorption of catalyst layer was measured using an apparatus similar to that of Mori et al [6]. The electrode (9 cm 2) contacting with phosphoric acid was maintained at 120 ~ for a week in air.…”
Section: Methodsmentioning
confidence: 99%
“…This is the exact reason for the poor cell performance especially with hydrogen/air. Mori et al [6] reported that the acid occupation under 350 ~ is affected by the undecomposed Triton X-100. However, from our results, it is confirmed that Triton X-100 was decomposed or evaporated completely from the catalyst layer under 250 ~ because of the catalytic action of platinum (results 5 and 6).…”
Section: Oxidation Of Support Carbonmentioning
confidence: 99%
See 2 more Smart Citations